Constraining Fossil Fuel CO2 Emissions From Urban Area Using OCO‐2 Observations of Total Column CO2. Issue 8 (15th April 2020) - Ye, Xinxin; Lauvaux, Thomas; Kort, Eric A.; Oda, Tomohiro; Feng, Sha; Lin, John C.; Yang, Emily G.; Wu, Dien
Abstract: Satellite observations of the total column dry‐air CO2 (XCO2 ) are expected to support the quantification and monitoring of fossil fuel CO2 (ffCO2 ) emissions from urban areas. We evaluate the utility of the Orbiting Carbon Observatory 2 (OCO‐2) XCO2 retrievals to optimize whole‐city emissions, using a Bayesian inversion system and high‐resolution transport modeling. The uncertainties of constrained emissions related to transport model, satellite measurements, and local biospheric fluxes are quantified. For the first two uncertainty sources, we examine cities of different landscapes: "plume city" located in relatively flat terrain, represented by Riyadh and Cairo; and "basin city" located in basin terrain, represented by Los Angeles (LA). The retrieved scaling factors of emissions and their uncertainties show prominent variabilities from track to track, due to the varying meteorological conditions and relative locations of the tracks transecting plumes. To explore the performance of multiple tracks in retrieving emissions, pseudo data experiments are carried out. The estimated least numbers of tracks required to constrain the total emissions for Riyadh (<10% uncertainty), Cairo (<10%), and LA (<5%) are 8, 5, and 7, respectively. Additionally, to evaluate the impact of biospheric fluxes on derivation of the ffXCO2 enhancements, we conduct simulations for Pearl River Delta metropolitan area. Significant fractions of local XCO2 enhancements associated with local biospheric XCO2 variations are shown, which potentially lead to biased estimates of ffCO2 emissions. We demonstrate that satellite measurements can be used to improve urban ffCO2 emissions with a sufficient amount of measurements and appropriate representations of the uncertainty components. Key Points: Inversion method is utilized to constrain whole‐city fossil fuel emissions with measurement and transport model errors considered Potential of incorporating multiple tracks to obtain regular emission estimates is evaluated by pseudo data experiments Significant contribution of the biospheric fluxes variability to local XCO2 variation is demonstrated